The Need for Rejuvenation of Forestry Sector - Chowdhary, R. L. (Indian Forester, 1979)
The social and economic worth or forestry resources is grossly understated in National income estimates, because of lack of data on outputs, prices and absence of market indicators for products and services like soil and climate a melioration etc. Although the sector has vast potentialities as generator of employment in rural areas, these have not been adequately tapped. The investment in afforestation of barren areas, plantations and development forest communication in the last four development plans have not been of sufficient stature to make a significant dent in to problems of meeting the chronic shortage of wood and other forest products. It is, therefore, necessary to review the forest planning strategies and prepare a comprehensive land use plan for all the areas yielding forest products & servies. It is equally important to estimate the demand and supply of forest products and establish long and short term production goals for government forests and lands available outside for forestry. The propulsive nature of forstry sector in promoting the growth and development of other sectors would not be fully realised, unless its production and utilization of outputs are propeorly integrated, both on regional and national basis and investment requirements are worked out for both the activities. A reappraisal of existing resources and the capacity of the sector to absorb fresh investment is quite germane to the issue of framing appropriate management policies and goals for the sector.